Financial accounting - Weetman, Pauline (Pearson Education, 2013)
This edition retains all of the classic features that have contributed to the book's success: clarity of expression, the focus on the accounting equation, student activities and real-life commentaries running through each chapter, and the inclusion of the Safe and Sure Annual Report as an example of a listed company.